2020
DOI: 10.1111/geb.13186
|View full text |Cite
|
Sign up to set email alerts
|

Soil dissolved organic carbon in terrestrial ecosystems: Global budget, spatial distribution and controls

Abstract: Aims: Soil dissolved organic carbon (DOC) is a primary form of labile carbon in terrestrial ecosystems, and therefore plays a vital role in soil carbon cycling. This study aims to quantify the budgets of soil DOC at biome and global levels and to examine the variations in soil DOC and their environmental controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 136 publications
4
48
0
Order By: Relevance
“…We further found that red grapes of Eurasian species were associated with higher biomass levels relative to similarly aged white grapes of Eurasian species (Figure 1), indicating that vineyards growing red grape varieties exhibit a higher carbon storage capacity than do those growing white grape varieties (Table 4). We further found that soil active organic carbon fractions (MBC and DOC) were mainly concentrated in the surface soil of the grapevine rhizosphere (Figure 3), indirectly suggesting that soil microorganisms are present primarily within this surface soil layer where most nutrient conversion and circulation is likely to occur, consistent with previous reports for other soil types [48][49][50][51].…”
Section: Discussionsupporting
confidence: 91%
“…We further found that red grapes of Eurasian species were associated with higher biomass levels relative to similarly aged white grapes of Eurasian species (Figure 1), indicating that vineyards growing red grape varieties exhibit a higher carbon storage capacity than do those growing white grape varieties (Table 4). We further found that soil active organic carbon fractions (MBC and DOC) were mainly concentrated in the surface soil of the grapevine rhizosphere (Figure 3), indirectly suggesting that soil microorganisms are present primarily within this surface soil layer where most nutrient conversion and circulation is likely to occur, consistent with previous reports for other soil types [48][49][50][51].…”
Section: Discussionsupporting
confidence: 91%
“…A standardized microbial data system that contains primary microbial variables with consistent measurement approach or after conversion is critical to reduce the bias associated with distinct methods (Xu et al, 2020). Last but not least, the observed data for bacterial and fungal biomass C commonly vary by more than five orders of magnitude (Guo et al, 2020;He et al, 2020;Sinsabaugh et al, 2016;Xu et al, 2013Xu et al, , 2017, while ecosystem-level variables commonly vary by less than three orders of magnitude. This large discrepancy makes the validation approach applied to ecosystem-level C pools and fluxes less robust in microbial models, as shown in this study of model validation (Section 3.1).…”
Section: Limitations and Improvementsmentioning
confidence: 99%
“…Climatic, edaphic, vegetation, and microbial variables were not fully reported in published studies, we extracted such variables from global datasets following our previous studies (Guo et al, 2020;He et al, 2020;Xu et al, 2013Xu et al, , 2017. For climatic variables, we extracted mean annual temperature (MAT) and mean annual precipitation (MAP) during 1970-2000 from the WorldClim database version 2 with the spatial resolution of 30 s (https://www.world clim.org/ data/world clim21.html).…”
Section: Climate Edaphic Vegetation and Microbial Datamentioning
confidence: 99%
“…The auxiliary datasets used included the global land area database and global vegetation distribution dataset. The global vegetation distribution dataset was obtained from a spatial map of 11 major biomes: boreal forest, temperate forest, tropical/subtropical forest, mixed forest, grassland, shrubland, tundra, desert, natural wetlands, cropland, and pasture, which have been used in our previous publications (Guo et al, 2020;He et al, 2020;Xu et al, 2013Xu et al, , 2017. The global land area database was from the surface data map of 0.5° × 0.5° generated for E3SM (https://web.lcrc.anl.gov/publi c/ e3sm/input data/lnd/clm2/surfd ata_map/).…”
Section: Climate Edaphic Vegetation and Microbial Datamentioning
confidence: 99%